Costituzione e discorso delle istituzioni in Cina oggi (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
In March 2018, the National People’s Congress of China adopted of the fifth amendment to the current constitutional text. In the five years prior to the vote, the CCP and state organs published a series of speeches and documents in order to reaffirm the centrality of the Constitution in the country’s political life. The Constitution hence became one of the keywords of political discourse and one central topic in news production by national and international media. After the adoption of the amendment, the flow of media communication on the topic spread rapidly into the realm of Chinese cultural and creative industry. This paper will map how the amendment adopted in 2018 was linked to a discursive framework, built on the consolidation of a genre repertoire aimed at reinforcing political stability and regime legitimacy in China.
Keywords: Cina; Constitution; discoursive framework; institutional discourse; genre set; genre repertoire